Modernization and Malay matrimonial foodways in the rural area / Mohd Syaquif Yasin Kamaruddin - Yasin Kamaruddin, Mohd Syaquif (2010)
Modernization is a global phenomena and closely associates with globalization and industrialization. It has influenced and altered every facets of human life not only the routines, traditions, rituals, norms but also the daily activities and specific occasion including matrimony or weddings practices. This study empirically investigates the impact of modernization on the Malays matrimonial or wedding foodways in the rural area specifically looking at two aspects; alteration in food preparation, consumption and the social community bond. Through combination of the qualitative (interview, observation) and quantitative (self-completed questionnaire) some meaningful insights on the issues investigated were obtained. Similar to urban, modernization slightly altered the Malay wedding foodways in the rural parallel with socio-economics, life styles and emergence of the modern equipments. This has given significant impact to the social bond or togetherness among the community.